2017
DOI: 10.3390/cli5030072
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Oklahoma City Urban Heat Island Effect Using a WRF/Single-Layer Urban Canopy Model, a Joint Urban 2003 Field Campaign, and MODIS Satellite Observations

Abstract: Abstract:The urban heat island effect (UHI) for inner land regions was investigated using satellite data, ground observations, and simulations with an Single-Layer Urban Canopy Parameterization (SLUCP) coupled into the regional Weather Research Forecasting model (WRF, http://wrf-model.org/ index.php). Specifically, using the satellite-observed surface skin temperatures (T skin ), the intensity of the UHI was first compared for two inland cities (Xi'an City, China, and Oklahoma City (OKC)), which have different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Jin et al (2005) (JI) thoroughly inspected the influence of the urban system on climate change [27]. In other previous studies [28][29][30][31] which analyzed the UHI effect extensively, the dependence of the UHI effect on the surface temperatures, albedos, and emissivity was demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Jin et al (2005) (JI) thoroughly inspected the influence of the urban system on climate change [27]. In other previous studies [28][29][30][31] which analyzed the UHI effect extensively, the dependence of the UHI effect on the surface temperatures, albedos, and emissivity was demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…(A-C) are summer, winter and Annual respectively. (Zhang H. Y. et al, 2017;Jiang et al, 2020). The fact that the data used in this study were collected for the inner city may explain why WIN was found to have a negative impact on precipitation in summer.…”
Section: Figurementioning
confidence: 97%
“…Recent advances in climate science and climate models such as the Weather Research and Forecasting (WRF) model allows researchers to downscale data to a resolution of 1km with relative accuracy, accounting for urban parameterizations and land use. As such, different urban parameterization schemes and local land cover data and their effects on the local UHI effect can be analysed [48,49]. Additionally, the effects of climate change and further development in urban areas can be studied through dynamic modelling, where global climate models following a climate change scenario can be dynamically downscaled to estimate what fraction of the increase in UHI intensity can be attributed to global warming or to urbanization [50].…”
Section: At Regional Scalesmentioning
confidence: 99%